Cultural Tourism in Kilicao, Daraga, Albay, Philippines for Community Development - Fernandez, Vicente (JPAIR Multidisciplinary Research, 2020)
Cultural tourism has a significant contribution to the economic growth of the community. The study aimed to (1) Establish the residents’ awareness of cultural tourism for community development in terms of (a) arts, (b) customs, and (c) traditions 2.) Determine the benefits of cultural tourism in Kilicao along the variables mentioned above (3) analyze the challenges encountered by the residents in developing the cultural tourism in the community, and 4.) Recommend programs to promote and develop cultural tourism in the community. The study employed the qualitative research method, and the focused-group discussion and interview were used to understand the fundamental reasons, opinions, and motivations. The findings revealed that the residents have expressed enthusiasm to actively participate and cooperate to promote cultural tourism in the community; there were benefits to the residents; the residents have encountered challenges, such as lack of knowledge, financial constraints, and accessibility issues; and programs were being offered towards community development. As recommended, tourism planning for the promotion should be done through community awareness programs. The local government unit should also allocate funds with the help of the different agencies for its sustainability.
Keywords: Bicol College; cultural tourism; promotion; sustainability; community; Philippines